2003
DOI: 10.1111/j.1574-6941.2003.tb01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and virulence of Flavobacterium psychrophilum in water microcosms

Abstract: Flavobacterium psychrophilum, the causative agent of rainbow trout fry syndrome and cold water disease in salmonids, causes serious disease outbreaks in fish farms worldwide. The aim of the present study was to examine the survival capacity of F. psychrophilum in laboratory microcosms containing sterilised water under different environmental conditions and to examine the virulence of starving F. psychrophilum cells. The results showed that F. psychrophilum survived for very long time in sterilised fresh water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 19 publications
2
36
1
Order By: Relevance
“…Potential mechanisms include fish and bird migrations but airborne dissemination may be another possibility. Indeed, F. psychrophilum is able to survive in pure water [39] and freshwater bacteria -including Flavobacteriaceae - were recently sampled in the upper troposphere [40]. Alternatively, genetic mixing can involve a succession of more frequent small-distance steps.…”
Section: Resultsmentioning
confidence: 99%
“…Potential mechanisms include fish and bird migrations but airborne dissemination may be another possibility. Indeed, F. psychrophilum is able to survive in pure water [39] and freshwater bacteria -including Flavobacteriaceae - were recently sampled in the upper troposphere [40]. Alternatively, genetic mixing can involve a succession of more frequent small-distance steps.…”
Section: Resultsmentioning
confidence: 99%
“…F. psychrophilum can survive in stream water for months and adopts a different morphology apparently to withstand the conditions of starvation [45]. Madetoja et al [46] showed that F. psychrophilum cells in freshwater at 15°C remained culturable through 300 days. Attachment to n-hexadecane and unfertilized eggs was significantly greater by F. psychrophilum cells maintained in either stream water or cytophaga broth for 1 month, in contrast to cells from 3-day-old cultures in cytophaga broth [45].…”
Section: Epizootiology and Transmissionmentioning
confidence: 98%
“…Greater studies are also required to investigate the presence and role of this VBNC state in microbial pathogens that cause disease in the aquatic natural setting such as in fish.Taking for example, Flavobacterium psychrophilum , the causative agent of rainbow trout fly syndrome and cold water disease in salmonids, where subpopulations were still culturable after starvation for 300 days in sterilised fresh water. The virulence of starved F. psychrophilum was maintained for at least 7 days after the transfer of the bacterial cells to fresh water [37]. The VNBC state was earlier reported for this fish pathogen by Madetoja and Wiklund [38] who revealed differences between enumeration using advanced immunoflourescence and genetic probes (i.e., nested PCR) compared to that of using traditional agar plate cultivation.…”
Section: Viable But Nonculturable Forms Of Waterborne Bacteriamentioning
confidence: 98%